The Impact of Liquidity on the Market Value of Saudi Joint Stock Companies through 2011-2020 - Al-Zahrani, Ali Khalaf Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the impact of liquidity on the market value of Saudi joint stock companies in the Kingdom of Saudi Arabia. The study used the descriptive analytical approach, and the research community consisted of all sectors of the Saudi market, and an intentional sample of the industrial companies affiliated to the capital goods and long-term goods sectors was selected (the number of their companies is (18) company.The study concluded that there is a negative and statistically significant impact of the trading ratio on the market value of the company, due to the amount of assets and its ability to cover liabilities, and it was found that there is a positive and statistically significant effect of the quick liquidity ratio on the market value, as the higher the quick liquidity ratio, the higher the market value of the company.The study recommended that the companies of the capital goods sector and the Saudi long-term goods sector listed in the Saudi capital market should follow appropriate policies to manage liquidity in an optimal way, because of the importance of liquidity in achieving the company’s goal and maximizing its profits, and the need for companies to pay attention to the capital goods sector and the Saudi long-term goods sector Listed in the Saudi money market in the list of cash flows and relying on the data contained therein when making investment and financing decisions, by raising efficiency in managing cash flow, as the cash flow list is prepared on a cash basis, and the need for companies in the capital goods sector and the long-term goods sector to Saudi Arabia listed in the stock market pays attention to the market value and the factors affecting it positively, and studying the negative influences and treating them.
Keywords: Liquidity; Market Value; Saudi Companies; Joint Stock